Modelling of Heat Transfer Through Hollow Blocks Produced with Rice-Husk-Ash Blended Cement. - Kamiyo, O. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Hollow sandcrete blocks are widely used in many countries of the world. In recent years, cement content is being partially substituted by admixtures especially agricultural wastes. Modeling of heat transfer characteristics of these modified blocks is essential in order to predict their thermal performance. This study focuses on this modeling with the aid of a finite-volume based computer code. Specifically, for regular, two-cavity blocks produced with the cement partially substituted with rice husk ash (RHA). The result showed that as the percentage substitution of RHA increased, thermal gradient across the width of the block increased, while the rate of heat flow reduced. The second part of the study examined the effect of heat transfer through the air-gap as compared to a similar study regarding it as vacuum. The heat flow through the air-gaps of the building bricks affected the pattern of heat flow within the bricks, hence, they could not be regarded as a vacuum. The results of this study will be useful to building professionals in the choice of building blocks and proper estimation of air- conditioning load in buildings.